Comparison of lateral vs. vertical marketing concepts in brand creation process - Malynka, Oksana; Perevozova, Iryna (Technology audit and production reserves, 2018)
The object of research is lateral marketing. This is a new marketing concept that allows to extend marketing toolkit beyond the sequential and logical process on which it is based, and help companies generate new ideas that neither consumers nor market research can offer. Traditional methods of deduction and induction, scientific classification and grouping, as well as empirical methods are used to compare the concepts of lateral and vertical marketing and discuss their role in the process of creating brands. It is revealed that lateral marketing is not above vertical – they complement each other. Moreover, lateral marketing can’t exist without vertical, because, sooner or later, competitors also appear in the new market category, with whom it is necessary again fight in order not to lose the leading positions. However, these are two different approaches that have many features and differences. When applying the concept of vertical marketing, all innovations will be created within a fixed market space. This is due to the fact that such innovations have a positive effect on the level of sales, because new potential buyers appear. However, these innovative strategies do not create new categories and markets. And as a result, the level of sales in conditions of too large segmentation grows by ten percent. Therefore, this approach to the creation of products very often can’t give the expected results. Under such conditions, the authors recommend using lateral marketing, as this is the most effective way to compete in “mature” markets, where microsegmentation and brand glut do not leave space for new opportunities. The principles of decision making in lateral marketing are very different. Creative and intuitive thinking works here. It is necessary to develop creativity in the company’s employees, to attract extraordinary personalities to the marketing departments.